Estandarización de una batería para la evaluación de factores de riesgo psicosociales laborales en trabajadores colombianos (2016)
A battery of questionnaires to assess psychosocial risk factors at work was developed in 2010 in response to Resolution 2646 created by the Colombian Ministry of Social Protection. However, this battery presents some theoretical and practical limitations. A new battery of instruments has been designed and validated that includes instruments and risk indicators of the demand-control-social support and the effort-reward imbalance models. Other factors, not included in these models, but that Resolution 2646 suggests should be assessed, have also been added, and with this additional information, the new battery allows us to also calculate a “global indicator” of demand, control, and social support; family and social risk conditions, coping and personality; and health and wellbeing. The new battery was administered to a sample of 16,095 workers from different occupations and representative Colombian regions. An analysis of the various domains indicates that internal consistency of the various scales is high. The new battery has the following properties: it is simple to use in paper format or when administered by computer, it enables comparison between occupations, it offers unified scores for each variable, and provides information to assess the risk factors suggested by Resolution 2646. In addition, it will make it possible to compare the results obtained when analyzing Colombian workers with those obtained from studies of workers from other countries.